Pemanfaatan Biomassa Alga Biru-Hijau Anabaena Cycadae Dalam Proses Biosorpsi Logam Cr Pada Limbah Cair Industri Elektroplating - Fanani, Adita Suri; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chromium (Cr) is a heavy metal that has a toxicity and the presence in waters caused by the disposal of wastewater from various industrial activities, one of them is electroplating industry. One of technology that can be applied to reduce the concentration of Cr in the electroplating industry wastewater is biosorption by using biomass of blue-green algae Anabaena cycadae. This research aims to reducing the concentration of Cr was analyzed using AAS on variation mass of biomass (0.1; 0.2; 0.3; and 0.4 grams), pH of wastewater (3,5, 7, and 9), and the detention time (30, 60, 90, and 120 minutes). The results showed the adsorption capacities of Cr concentration was highest in mass of biomass 0.1 grams, pH 7, and detention time of 60 minutes is 4,492 mg Cr / g biomass.Keywords: Biosorption, algae biomass, biosorbent mass, pH, contact time, Cr, electroplating wastewater